Pengelolaan Program Pelatihan Kursus Komputer Microsoft Office di Lembaga Kursus GOLEVAT Kota Semarang - Bhakti Kusuma Wardani (Lifelong Education Journal, 2023)
Courses and training are needed with the aim of increasing the competency skills of an individual or community group in non-formal education. One of the abilities needed in this era is the ability to have computer skills with Microsoft Office programs. The GOLEVAT Institute as a forum for organizing community competency capacity building that focuses on the field of digital computer technology. The implementation of a program requires a structured and planned management to achieve the goals that have been set. This study aims to describe the management of the Microsoft Office computer course training program at the GOLEVAT course in Semarang City which includes planning, implementation, and evaluation as well as describing the supporting and inhibiting factors of the program. The design used in this study is to use a type of qualitative research. Research informants included five people consisting of one Founder, two teaching instructors, and two program participants. The founder here is the main informant in this study and the other informants are supporting informants. The data validation technique used in this research is source triangulation and technical triangulation, this triangulation starts from analyzing the data using data collection, reduction, presentation and conclusion methods. The results of the study show that in the management of Microsoft Office computer course training programs, there are three main functions of management, namely planning which includes the formulation of background objectives, determining teacher coordination, setting location and time targets related to program costs, using Microsoft standard material modules, selecting media , determination of delivery methods, preparation of facilities and infrastructure. Implementation includes activities using media, modules, and methods that have been planned, motivating participants to be able to take part in the course. Program evaluation through practice questions to get a competency certificate. Evaluation of teachers, modules and media facilities through the Google form link which is filled in directly by participants after the program is finished which is used as a reference for the leadership to evaluate and improve institutions and programs. The supporting factors for the Microsoft Office computer training course program are the interest of the participants, competent instructors, and supporting media facilities. The inhibiting factor for the participants was forgetting the formula, for the teacher it was the increase in vehicle fuel rates. The advice that can be given by researchers is that there should be official recruitment of teachers and evaluations carried out in a structured and scheduled manner, then the material is always updated in accordance with increasingly advanced technological developments.